PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN RELAWAN PEMADAM KEBAKARAN DI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA BENGKULU - Anisa, Ragilia Fitri; Evsa Wulan Suri; Hernowo Novi Yanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research aims to find out the quality of public service at Ujan Mad District Office Kepahiang Regency and factors that affect the quality of public services at Ujan Mas District Office Kepahiang Regency. This research is a descriptive research with qualitative approachment. Key informant in this research is head of public service at Ujan Mas District Office Kepahiang Regency. Support informant consist of Ujan Mas District people. Data gathering use observation, interview, and documentation. Data analysis use data gathering, data reduction, and data presentation. Data validity use source triangulation technique and triangulation technique. The results showed the following : the quality of public service at Ujan Mas District Office Kepahiang Regency (a) Tangible dimension at Ujan Mas Districts implement yet in place concerning comfort, related with the place comfort, easy of service, officer’s discipline, easy of acces and tools using. (b) Reliability dimension at Ujan Mas District is less in service standart that not clear yet, the ability of officers are still lacking and there are the costs of bureaucracy. (c) Assurance dimension at Ujan Mas District yet have uptime guarantee for users of the service and still charging for the bereaucracy in the ministry. (d) Emphaty dimension, the officers serve people kindly and politely ,but officers still priopritize their self interest than service user’s importance. and Factors that influence public service quality at Ujan Mas District Office Kepahiang Regency is internal and external factors. The internal factors is the infrastructure that do not satisfy yet, the less of service officers, and tools. External factors is service system and service preparing system that not maximum yet.